Task-related trunk training on balance, trunk control, pulmonary function and quality of life in patients with Parkinson's disease. A randomised controlled trial. (2nd March 2022) - Akhila, RM; Karthikbabu, Suruliraj; Mohan, Divya; Prem, Venkatesan; Roy, Ajith Kumar
Abstract : Background/Aims: Stooped posture and 'en-bloc' movement of the trunk in people with Parkinson's disease are related to balance issues, pulmonary dysfunction and difficulty in daily tasks. The primary objective of this study was to examine the effects of task-related trunk training on balance in people with Parkinson's disease. The secondary objective was to observe whether trunk control, thoracic rotation range, pulmonary function and quality of life would change for patients with Parkinson's disease after trunk training. Methods: A total of 32 individuals participated in this randomised controlled trial. They had a mean age of 70.8 years, with a modified Hoehn and Yahr Scale grade of 1.5–3, could take more than six steps in the 360° turn test, were scored as grade I or II on the retropulsion test and had an absence of severe cognitive deficits. Task-related trunk training emphasised the thoracic spine's extension and rotation in prone position on elbows, hands and knees and in kneeling, sitting and standing positions. Standard physiotherapy included breathing exercises, stretching of shoulder and neck muscles, balance and walking training. Both groups practised for 1 hour a day, 3 days a week over 6 weeks. The primary outcome measure was the Mini-Balance Evaluation Systems Test. The secondary outcome measures were the Trunk Control Test, thoracic rotation range of movement, Pulmonary Function Test and Parkinson's Disease Questionnaire-39. Results: Repeated measure analysis of variance revealed significant group by time interaction for the Mini-Balance Evaluation Systems Test and thoracic rotation range ( P <0.05), but not for the pulmonary function test and quality of life measures. Conclusions: Task-related trunk training appears to be more beneficial in the balance capacity of individuals with Parkinson's disease than standard physiotherapy, but does not have any significant effects for pulmonary function and health-related quality of life.